2020
DOI: 10.1523/jneurosci.1284-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-Dependent Copper Homeostasis Sustains Synaptic Development and Mitochondrial Content

Abstract: Rare genetic diseases preponderantly affect the nervous system causing neurodegeneration to neurodevelopmental disorders. This is the case for both Menkes and Wilson disease, arising from mutations in ATP7A and ATP7B, respectively. The ATP7A and ATP7B proteins localize to the Golgi and regulate copper homeostasis. We demonstrate genetic and biochemical interactions between ATP7 paralogs with the conserved oligomeric Golgi (COG) complex, a Golgi apparatus vesicular tether. Disruption of Drosophila copper homeos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 123 publications
(196 reference statements)
1
21
0
Order By: Relevance
“…The downregulation of COG complex subunits can rescue the altered synaptic phenotypes. These results collectively support the critical role of Golgi and Cu in neurodegeneration and neurodevelopmental disorders [ 131 ].…”
Section: Membrane Compartments and Their Communications Involved In Regulating Intracellular Cu Homeostasissupporting
confidence: 80%
See 2 more Smart Citations
“…The downregulation of COG complex subunits can rescue the altered synaptic phenotypes. These results collectively support the critical role of Golgi and Cu in neurodegeneration and neurodevelopmental disorders [ 131 ].…”
Section: Membrane Compartments and Their Communications Involved In Regulating Intracellular Cu Homeostasissupporting
confidence: 80%
“…Evidenced by using the Drosophila model, Hartwig et al demonstrated that interactions between ATP7 paralogs and COG complex, a Golgi apparatus vesicular tether, are essential to maintain Cu homeostasis in neurons. Disruption of ATP7–COG complex interaction affects COG-mediated TGN proteins recycling in motor neurons, which is similar to manipulating the expression level of ATP7 paralogs, leading to the perturbation of Cu homeostasis, decreased synaptic mitochondria content and altered synapse plasticity [ 131 ].…”
Section: Membrane Compartments and Their Communications Involved In Regulating Intracellular Cu Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol bypasses challenges because of limited sample amounts and facilitates studies examining the biological roles of metals in health and disease. For complete details on the use and execution of this protocol, please refer to Hartwig et al. (2020) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Hartwig et al. (2020) .…”
mentioning
confidence: 99%